Globalization, Market Power, and the Natural Interest Rate - Natal, Jean-Marc (IMF Working Papers; Working Paper ;, 2019)
We argue that strong globalization forces have been an important determinant of global real interest rates over the last five decades, as they have been key drivers of changes in the natural real interest rate-i.e. the interest rate consistent with output at its potential and constant inflation. An important implication of our analysis is that increased competition in goods and labor market since the 1970s can help explain both the large increase in real interest rates up to the mid-1980s and-as globalization forces mature and may even go into reverse, leading to incrementally rising market power-its subsequent and protracted decline accompanied by lower inflation. The analysis has important implications for monetary policy and the optimal pace of normalization.